Yaks yak : animal word pairs - Park, Linda Sue (Clarion Books, Houghton Mifflin Harcourt, 2016)
Presents animals acting out the verbs made from their names, including hogs hogging, slugs slugging, and other creatures demonstrating homographs, words with different meanings that are spelled and pronounced the same.